German Nuclear Policy Reconsidered: Implications for the Electricity Market - Michaela Fürsch; Dietmar Lindenberger; Raimund Malischek; Stephan Nagl; Timo Panke; Johannes Trüby (Institute of Energy Economics at the University of Cologne (EWI), 2011)
In the aftermath of the nuclear catastrophe in Fukushima, German nuclear policy has been reconsidered. This paper demonstrates the economic effects of an accelerated nuclear phase-out on the German electricity generation sector. A detailed optimization model for European electricity markets is used to analyze two scenarios with different lifetimes for nuclear plants (phase-out vs. prolongation). Based on political targets, both scenarios assume significant electricity demand reductions and a high share of generation from renewable energy sources in Germany. Our principal findings are: First, nuclear capacities are mainly replaced by longer lifetimes of existing coal-fired plants and the construction of new gas-fired plants. Second, fossil fuel-based generation and power imports increase, while power exports are reduced in response to the lower nuclear generation. Third, despite the increased fossil generation, challenging climate protection goals can still be achieved within the framework of the considered scenarios. Finally, system costs and electricity prices are clearly higher. We conclude that the generation sector can generally cope with an accelerated nuclear phase-out under the given assumptions. Yet, we emphasize that such a policy requires a substantial and costly transformation of the supply and the demand side.
Keywords: C61; L94; Q48; Q58; 330; Nuclear policy; climate protection; renewable energy; electricity market modeling